The representation of mature adults in TV commercials: A cross-cultural content analysis of portrayals in Poland and in the U.S. - Kinga Kowalewska; Erika Grodzki (Annales Etyka w Życiu Gospodarczym, 2019)
The aim of the article is to examine the portrayals of mature adults (55+) in television commercials in Poland and in the United States. It is important to analyze the portrayal of this group as, on the one hand, they are a lucrative and growing consumer market, however, on the other hand, past studies have shown that this segment has been often stereotyped and underrepresented. It is hypothesized that due to clear differences in the value systems and socio-economic characteristics of both countries, the representation of the mature segment of consumers will differ significantly in terms of their overall portrayal. A purposive sample of 15 Polish commercials and 15 U.S. commercials was selected since the researchers wished to focus on particular portrayals rather than analyze a large sample of commercials. The method was a comparative content analysis. Each commercial was examined particularly for the social context, the activities performed by the individuals, gender representation, health status, race, image, role and product/service type. The findings showed that older people play various roles, however, cultural values and differences were evident in the commercials placed in both countries. This could be seen in the content and focus of the ads.